Syngas production from palm kernel shell and polyethylene waste blend in fluidized bed catalytic steam co-gasification process - Moghadam, R.; Yusup, S.; Uemura, Y.; Chin, Bridgid; Lam, H.; Al Shoaibi, A. (Pergamon, 2014)
Energy from renewable source is expected to complement the energy derived from fossil fuel resources. Gasification is a versatile thermochemical process for solid waste fuel conversion. In the current paper, syngas production from palm kernel shell (PKS) and polyethylene waste blend in a catalytic steam gasification process is studied. In order to acquire the optimum condition of syngas production, the effect of main variables such as reaction temperature, steam/feedstock (S/F) ratio, polyethylene waste/biomass (P/B) ratio on syngas production was investigated and optimized via Taguchi design of experiment approach. Under the optimized condition of 800 °C, P/B ratio: 0.3 w/w and S/F ratio: 1 w/w, the total syngas yield and hydrogen yield achieved are 422.40 g syngas/kg feedstock and 135.27 g H2/kg feedstock, respectively.